The skills of a sports journalist in professional and professional journalistic work A field study for Al-Haddaf Al-Riyadi channel - mekhalif, fares; bendakfal, rachid (sports creativity, 2025)
The study aims to know the level of the work of the sports journalist in TV sports quotas and to reveal his relationship with each of the three factors - the educational level and the cultural level of the journalist and be able to employ modern technology - to achieve excellence and achieve success for these journalistic work and the extent of their access to professionalism, and The researcher has assumed that there is a relationship between the skills of the sports journalist in completing the journalistic work and the transition from the hobby to the professionalism achieved by TV sports quotas. The study was conducted according to three axes related to the correlation of professionalism in business with the educational level first, then its correlation with the cultural level and the journalist's knowledge of current events, and finally the extent of the journalist's ability to employ modern technology in his favor through access to professionalism